Analisis Perbandingan Kinerja TCP Vegas Dan TCP New Reno Menggunakan Antrian Random Early Detection Dan Droptail - Guntur Wahyu Pamungkas; Widhi Yahya; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Abstract Transmission Control Protocol (TCP) is a protocol on transport layer that have reliable properties in sending data. But reliable transmission can be distruped due congestion which are caused by increased traffic data. The problem can be solved by applying the correcrt TCP and queue management. In this research will be done simulation by comparing TCP Vegas and TCP New Reno by adding Random Early Detection and Droptail with scheme the addition of minthresh, max thresh and buffer capacity. After this research is done will get TCP and queue management that has the best performance in over coming congestion. The test results show, TCP Vegas is better than TCP NewReno with Random Early Detection, especially in packet delivery ratio, delay and packet drop. The results of packet delivery ratio test, TCP Vegas has the best performance when using Random Early Detection and Droptail with the average 99.9968% versus 99.6768% for TCP NewReno. The results throughput test, TCP NewReno has the best performance when using Droptail with the average 100749.4234kbps versus 94576.815kbps for TCP Vegas. The results delay test, TCP Vegas has the best performance when using Random Early Detection with the average of 4.31ms versus 5.98ms for TCP NewReno. And results packet drop test, TCP Vegas has the best performance when using Random Early Detection with the average 0.0002% versus 0.319% for TCP NewReno.